2011
DOI: 10.1038/npp.2011.190
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of MeCP2 Phosphorylation in the CNS by Dopamine and Serotonin

Abstract: Systemic administration of amphetamine (AMPH) induces phosphorylation of MeCP2 at Ser421 (pMeCP2) in select populations of neurons in the mesolimbocortical brain regions. Because AMPH simultaneously activates multiple monoamine neurotransmitter systems, here we examined the ability of dopamine (DA), serotonin (5-HT), and norepinephrine (NE) to induce pMeCP2. Selective blockade of the DA transporter (DAT) or the 5-HT transporter (SERT), but not the NE transporter (NET), was sufficient to induce pMeCP2 in the CN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 65 publications
(88 reference statements)
1
26
0
Order By: Relevance
“…2). Hutchinson et al [81] demonstrated that phosphorylation of MECP2 is dependent on dopamine, serotonin and norepinephrine activated pathways (Fig. 2, MECP2 phosphorylation).…”
Section: The Most Important Metabolites Genes and Pathways Affected mentioning
confidence: 99%
“…2). Hutchinson et al [81] demonstrated that phosphorylation of MECP2 is dependent on dopamine, serotonin and norepinephrine activated pathways (Fig. 2, MECP2 phosphorylation).…”
Section: The Most Important Metabolites Genes and Pathways Affected mentioning
confidence: 99%
“…Because psychostimulants such as cocaine and amphetamine act on the monoamine neurotransmitter system, the differential roles of dopamine (DA), serotonin (5-HT), and norepinephrine (NE) have been investigated. Although enhanced NE signaling failed to induce pS421 MeCP2, individual activation of DA or 5-HT sufficiently evoked MeCP2 phosphorylation (Deng et al, 2010;Hutchinson et al, 2011). It turned out that DA and 5-HT independently induce pS421 MeCP2 in selective brain regions and a combination of agents targeting specific classes of DA and 5-HT receptors could alone reproduce the pS421 MeCP2 pattern of amphetamine.…”
Section: Mecp2 Phosphorylation In Drug Addictionmentioning
confidence: 96%
“…Such type of integration also appears to be responsible for the neuronal subtype specificity of AMPH-induced S421 phosphorylation in the NAc. AMPH activates multiple monoamine neurotransmitter systems, among which activation of the dopamine (DA) and serotonin (5-HT) systems, but not the norepinephrine (NE) system, are sufficient to induce S421 phosphorylation (Hutchinson et al, 2012a). A separate study by Mao et al (2011) has implicated the NMDA receptor as the mediator of cocaine-induced S421 phosphorylation in the dorsal, but not the ventral striatum.…”
Section: Regulation Of Mecp2 Phosphorylationmentioning
confidence: 99%
“…RTT patients develop anxiety, aggression, and mood alterations (Chahrour and Zoghbi, 2007), accompanied with reduced levels of dopamine and serotonin (5-HT) metabolite (Fyffe et al, 2008). The activation of dopamine or 5-HT receptor is sufficient to induce MeCP2 S421 phosphorylation in NAc (Hutchinson et al, 2012a). Antidepressants, such as imipramine, increase the extracellular levels of monoamine neurotransmitters and induce S421 phosphorylation selectively in GABAergic interneurons of the ventral structure of nucleus accumbens (NAc) (Hutchinson et al, 2012b).…”
Section: In Vivo Function Of Mecp2 Phosphorylationmentioning
confidence: 99%